Achieving a more effective concentric braced frame by the double-stage yield BRB. (1st May 2019) - Barbagallo, F.; Bosco, M.; Marino, E.M.; Rossi, P.P.
Highlights: The DYB is proposed as a brace member to obtain an improved steel CBF. The benefits of the mechanical features of DYB on the frame response is studied. A method for the design of the components of the new CBF is formulated. The design method is consistent with the architecture of EC8. The behaviour factor is calibrated to fulfil the performance requirements of EC8. Abstract: The steel Concentric Braced Frame (CBF) is a popular structural type for buildings in seismic areas. In fact, it can conveniently provide the building with large strength and stiffness. Furthermore, the simplicity of fabrication that derives from the use of shear connections between beams and columns appeals to structural designers. Unfortunately, the dissipation capacity of steel braces is limited and the structural type is low redundant and thus prone to storey collapse mechanisms. To improve the seismic performance of the CBF double-stage BRBs (DYBs) could be used instead of conventional steel braces. The DYB exhibits high dissipative and stable cyclic response and, if inserted into a steel frame, promote the spread of damage owing to the shape of its hysteresis loop. Despite its qualities, in literature there are no design methods that allow its use. Hence, in this paper, a design method for steel frames with DYBs is formulated in compliance with the principles of the European seismic code. The behaviour factor q is calibrated to meet the performance objectives of Eurocode 8. The calibration is performed by nonlinear dynamic analysis conducted with OpenSees on 75 frames with different features. The numerical model is calibrated on the results of the experimental tests performed by Pan and his co-workers at Tsinghua University in Beijing (China). The deduced results confirm the effectiveness of the frame with DYBs, which can be designed with q values greater than those used for traditional steel braced frames.